2016
DOI: 10.1530/joe-15-0367
|View full text |Cite
|
Sign up to set email alerts
|

Activin A and follistatin during the oestrous cycle and early pregnancy in ewes

Abstract: The activin pathway has been postulated to be involved in regulation of multiple reproductive processes important for survival of the conceptus. These processes include luteinisation of the follicular cells and thus function of the corpus luteum, early embryo development and uterine function including implantation of the conceptus. Therefore, the aim of the current study was to determine whether the concentrations of activin A and follistatin (FST), an activin-binding protein, differed between ewes with a life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…RNAscope analysis confirmed that the transcript was mostly expressed by mural granulosa cells of antral follicles while qPCR quantification found it to be highest in proestrus and quickly and significantly downregulated in estrous. In contrast we found that the Activin A protein remained elevated in the blood in both proestrus and estrus, which is consistent with studies in other species such as ewes (O’Connell et al 2016). We speculate that this pattern may reflect a delay between transcription and translation, a buildup of the Activin A protein in the circulation, and the incorporation of the Inhba product into other dimers such as Inhibin A (Gedeon and Bokes 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…RNAscope analysis confirmed that the transcript was mostly expressed by mural granulosa cells of antral follicles while qPCR quantification found it to be highest in proestrus and quickly and significantly downregulated in estrous. In contrast we found that the Activin A protein remained elevated in the blood in both proestrus and estrus, which is consistent with studies in other species such as ewes (O’Connell et al 2016). We speculate that this pattern may reflect a delay between transcription and translation, a buildup of the Activin A protein in the circulation, and the incorporation of the Inhba product into other dimers such as Inhibin A (Gedeon and Bokes 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Activin A is a secreted protein homodimer translated from the Inhba transcript that is a crucial modulator of diverse ovarian functions including pituitary feedback, whose expression level depends highly on the stage of the estrous cycle (84). Quantification of Activin A protein in the serum by ELISA revealed elevated levels in the blood during both proestrus and estrus, which is consistent with studies in other species such as ewes (85). Importantly, the protein product of Inhba , the inhibin beta-A subunit, can be incorporated into other protein dimers, such as Activin BA, and Inhibin A, which were not measured in this study and may also represent cycling biomarkers.…”
Section: Discussionsupporting
confidence: 89%
“…We found IGFBP1 and IGFBP2 as main markers of LE as described before [ 49 , 51 ], whereas others have reported a widespread distribution in the endometrium [ 47 ]. Besides these well-known markers, LE expressed other genes, for which little is known in the bovine, encoding proteinase inhibitors involved either in the immune system, such as SLPI and A2M [ 52 , 53 ], in the regulation of uterine glycocalyx ( ITIH4) [ 54 ] or in the activin pathway controlling the development of conceptus ( FST) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study determined that the presence of exogenous follistatin in porcine COCs cultured in maturation medium markedly decreased the developmental competence of oocytes without affecting early cleavage. Several studies have demonstrated that follistatin, an activin‐binding protein (O'Connell et al., ), neutralized the effect of activin A and reduced the developmental competence of matured oocytes in vitro (Silva & Knight, ). Conversely, the addition of only activin A to oocyte maturation medium did not affect nuclear maturation, but increased the development of cumulus‐enclosed and denuded oocytes after embryonic cleavage (Silva & Knight, ; Stock, Woodruff, & Smith, ).…”
Section: Discussionmentioning
confidence: 99%